2014
DOI: 10.1371/journal.pntd.0003324
|View full text |Cite
|
Sign up to set email alerts
|

Patients' Perceptions on the Performance of a Local Health System to Eliminate Leprosy, Paraná State, Brazil

Abstract: BackgroundIn Brazil, leprosy has been listed among the health priorities since 2006, in a plan known as the “Pact for life” (Pacto pela Vida). It is the sole country on the American continent that has not reached the global goal of disease elimination. Local health systems face many challenges to achieve this global goal. The study aimed to investigate how patients perceive the local health system's performance to eliminate leprosy and whether these perceptions differ in terms of the patients' income.Methodolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
10

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 26 publications
2
11
0
10
Order By: Relevance
“…The evidence of integrated health approach in reducing stigma is shown by a study in India where 50% reduction in level of stigma was found with community participation in leprosy control program [ 27 ]. Furthermore, a study in Brazil shows the main challenges in leprosy control program as lack of leprosy care at local health services and social mobilization of the community to leprosy control program [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The evidence of integrated health approach in reducing stigma is shown by a study in India where 50% reduction in level of stigma was found with community participation in leprosy control program [ 27 ]. Furthermore, a study in Brazil shows the main challenges in leprosy control program as lack of leprosy care at local health services and social mobilization of the community to leprosy control program [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study's ndings promote location-speci c nancial support schemes for leprosy patients and their carers, to shield from continuous nancial setbacks. Food vouchers in other Brazilian states, [104] and direct income replacement in Nigeria and China [105,106] have shown promise, and therefore could be trialled in Pernambuco. Superior to nancial or material help, vocational skills and disability-friendly workplace environments may enable patients and carers to permanently escape this socioeconomic vicious cycle, improving TOs [107].…”
Section: External Factorsmentioning
confidence: 99%
“…Cross-sectional study carried out in Londrina, Brazil, showed that people with leprosy had used the primary health care services, but did not receive the diagnosis of leprosy in these services (4) . Although there were advances in protocols of care for people with leprosy, there is the absence of collective action and involvement of families of people with the disease and the community.…”
Section: Introductionmentioning
confidence: 99%
“…Although there were advances in protocols of care for people with leprosy, there is the absence of collective action and involvement of families of people with the disease and the community. Therefore, besides the difficulty of diagnosis and treatment in primary care services, they also highlight perspectives limited to individual care and that does not cause social mobilization for disease control (4) .…”
Section: Introductionmentioning
confidence: 99%